A new hypothesis for Parkinson’s disease pathogenesis: GTPase-p38 MAPK signaling and autophagy as convergence points of etiology and genomics - Obergasteiger, Julia; Frapporti, Giulia; Pramstaller, Peter P.; Hicks, Andrew A.; Volta, Mattia (Molecular neurodegeneration, 2018)
The combination of genetics and genomics in Parkinson´s disease has recently begun to unveil molecular mechanisms possibly underlying disease onset and progression. In particular, catabolic processes such as autophagy have been increasingly gaining relevance as post-mortem evidence and experimental models suggested a participation in neurodegeneration and alpha-synuclein Lewy body pathology. In addition, familial Parkinson´s disease linked to LRRK2 and alpha-synuclein provided stronger correlation between etiology and alterations in autophagy. More detailed cellular pathways are proposed and genetic risk factors that associate with idiopathic Parkinson´s disease provide further clues in dissecting contributions of single players. Nevertheless, the fine-tuning of these processes remains elusive, as the initial stages of the pathways are not yet clarified. In this review, we collect literature evidence pointing to autophagy as the common, downstream target of Parkinsonian dysfunctions and augment current knowledge on the factors that direct the subsequent steps. Cell and molecular biology evidence indicate that p38 signaling underlies neurodegeneration and autoptic observations suggest a participation in neuropathology. Moreover, alpha-synuclein and LRRK2 also appear involved in the p38 pathway with additional roles in the regulation of GTPase signaling. Small GTPases are critical modulators of p38 activation and thus, their functional interaction with aSyn and LRRK2 could explain much of the detailed mechanics of autophagy in Parkinson´s disease. We propose a novel hypothesis for a more comprehensive working model where autophagy is controlled by upstream pathways, such as GTPase-p38, that have been so far underexplored in this context. In addition, etiological factors (LRRK2, alpha-synuclein) and risk loci might also combine in this common mechanism, providing a powerful experimental setting to dissect the cause of both familial and idiopathic disease.